SALINIZATION OF GROUNDWATER IN ARID AND SEMI-ARID ZONES: AN EXAMPLE FROM TAJARAK, WESTERN IRAN - Jalali M. (My University, 2007)
Study of the groundwater samples from Tajarak area, western Iran, was carried out in order to assess their chemical compositions and suitability for agricultural purposes. All of the groundwaters are grouped into two categories: relatively low mineralized of Ca–HCO3 and Na–HCO3 types and high mineralized waters of Na–SO4 and Na–Cl types. The chemical evolution of groundwater is primarily controlled by water–rock interactions mainly weathering of aluminosilicates, dissolution of carbonate minerals and cation exchange reactions. Calculated values of pCO2 for the groundwater samples range from 2.34 × 10−4 to 1.07 × 10−1 with a mean value of 1.41 × 10−2 (atm), which is above the pCO2 of the earth’s atmosphere (10−3.5). The groundwater is oversaturated with respect to calcite, aragonite and dolomite and undersaturated with respect to gypsum, anhydrite and halite. According to the EC and SAR the most dominant classes (C3-S1, C4-S1 and C4-S2) were found. With respect to adjusted SAR (adj SAR), the sodium (Na+) content in 90% of water samples in group A is regarded as low and can be used for irrigation in almost all soils with little danger of the development of harmful levels of exchangeable Na+, while in 40 and 37% of water samples in group B the intensity of problem is moderate and high, respectively. Such water, when used for irrigation will lead to cation exchange and Na+ is adsorbed on clay minerals while calcium (Ca2+) and magnesium (Mg2+) are released to the liquid phase. The salinity hazard is regarded as medium to high and special management for salinity control is required. Thus, the water quality for irrigation is low, providing the necessary drainage to avoid the build-up of toxic salt concentrations.
Keywords: SALINIZATION; GROUNDWATER; IRRIGATION; IRAN; ARID AND SEMIARID